Efektivitas Dental Health Education dengan Metode Demonstrasi terhadap Peningkatan Pengetahuan Menyikat Gigi Siswa Sekolah Dasar (e-GiGi, 2025)
Abstract: Dental caries is still a health problem experienced by many children in Indonesia. One of the factors that influence dental caries is behavioral factor. Changing behavior can be done by intervening through dental health education, especially about tooth brushing. One method that encourages the target to participate actively and involves many senses is the demonstration method. This study aimed to find out the effectiveness of dental health education (DHE) accompanied by demonstration method on increasing knowledge of tooth brushing among elementary school students. This was a quasi-experimental study with a non-equivalent control group design, using pretest and posttest for the treatment and control groups that were already determined. Samples were 100 students of SD Advent Paal 2 Manado, divided into two equal groups: control group (DHE without demonstration method) and treatment group (DHE with demonstration method). The Wilcoxon test showed that the p-value of dental health education with or without demonstration method was 0.000 (p